2000
DOI: 10.1021/ol0063104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competing Alkali Metal Cations on Neutral Host's Anion Binding Ability

Abstract: Anion binding by neutral hosts in organic solvents can be inhibited by the presence of alkali metal cations. The binding inhibition is due to salt ion-pairing which increases in the order Cs(+) < K(+) < Na(+). The binding inhibition can be reversed by using heteroditopic hosts that simultaneously bind both the metal cation and the anion. The largest cation-induced enhancements are observed with the less basic anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 23 publications
2
79
0
3
Order By: Relevance
“…[20] An advantage of an ion-pair receptor over a simple ion receptor is that the number of competing interactions in solution (i.e., the formation of cation-anion pairs) is reduced. [21] Recently, we reported that simple mesooctamethylcalix[4]pyrrole (1) has the ability to bind ion pairs in the solid state; [22,23] these complexes consisted of a cone conformation in which the pyrrolic NHs were hydrogen bonded to the anion on one face of the macrocycle and the resulting electron-rich cavity, formed on the opposite face, contained either a cesium, imidazolium or pyridinium cation. Solvent-extraction studies, involving the use of water and nitrobenzene, provided evidence for the formation of 1:1:1 cesium/calix[4]pyrrole/ halide ion-paired complexes in the organic phase (halide = chloride or bromide).…”
Section: Introductionmentioning
confidence: 99%
“…[20] An advantage of an ion-pair receptor over a simple ion receptor is that the number of competing interactions in solution (i.e., the formation of cation-anion pairs) is reduced. [21] Recently, we reported that simple mesooctamethylcalix[4]pyrrole (1) has the ability to bind ion pairs in the solid state; [22,23] these complexes consisted of a cone conformation in which the pyrrolic NHs were hydrogen bonded to the anion on one face of the macrocycle and the resulting electron-rich cavity, formed on the opposite face, contained either a cesium, imidazolium or pyridinium cation. Solvent-extraction studies, involving the use of water and nitrobenzene, provided evidence for the formation of 1:1:1 cesium/calix[4]pyrrole/ halide ion-paired complexes in the organic phase (halide = chloride or bromide).…”
Section: Introductionmentioning
confidence: 99%
“…The capsules 1×2 are based on two halfspheres: cavitand 2, functionalized with four azinium substituents, and calix [4]arene 1, containing four sulfonate substituents. Four pyridinium-sulfonate interactions bring the two halfspheres together to form a capsule ( Figure 1).…”
Section: Synthesis and Confirmation Of The Capsule Structurementioning
confidence: 99%
“…This strategy relies first on the selective 1,3-disubstitution of a para-tert-butylcalix [4]arene with a suitable asymmetric precursor (i.e., 6-8), followed by hydrazine-mediated cleavage of the phthalimide protecting groups. The resulting bisamines 12-14 were cyclized with suitable bis(acid chloride)s in moderate to high yields to afford the macrobicycles [15][16][17][18][19]. Oxidation of these macrobicycles with thalliumA C H T U N G T R E N N U N G (III) trifluoroacetate [14] gave the new heteroditopic calix[4]diquinone receptors 1-5 in yields of 42-89 %.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The affinity of the receptor for a single ion is defined by the processes K 1(cation) and K 3(anion) , Scheme 2. Synthesis of receptors 1-5.…”
Section: Introductionmentioning
confidence: 99%